Transformasi Nitrogen dalam Tanah Tergenang: Aplikasi Jerami Padi dan Kompos Jerami Padi - Lilik Tri Indriyati; Supiandi Sabiham; Latifah Kosim Darusman; Rykson Situmorang; . Sudarsono; Widjang Herry Sisworo (JOURNAL OF TROPICAL SOILS, 2008)
The use of organic materials aimed at reducing the dependence on inputs such as chemical fertilizers can contribute to sustainability and improving the low N fertilizer efficiency of rice plants in paddy soils.  Therefore, better understanding of N transformation in flooded soils, particularly the microbial transformation of N-organic amendments to plant-available N and gaseous N forms is needed for most efficient use of soil and organic materials N, for determining the potential of denitrification and for aiding in the selection of N management practices for sustainable agriculture.  The experiments were conducted in the laboratory and glasshouse of Soil Department, Faculty of Agriculture, Bogor Agricultural University.  An incubation experiment was conducted in the laboratory at room temperature during 120 d to analyze the mineralization-immobilization patterns in flooded soils amended with rice straw, rice straw composts 4 mo and 8 mo and their combinations with urea.  The first time of soil flooding, mineral N (N-NH4+ and N-NO3-) concentrations in all of the amended soils sharply decreased and those gradually increase since 7 d of incubation.  It might be due to the reduction of N-NO3- to N2O and N2, and immobilization.  This data was consistent with the data of N2O emission derived from pot experiment.  The high emission of N2O was observed at the first time of soil flooding of the amended soils, and the soils added rice straw showed the largest N2O emission than the other treatments. It might be due to the change of soil condition from aerobic to anaerobic condition, and the higher decomposable C as energy source for denitrifyer contained in rice straw.  Regardless the organic materials added to soils, the longer anaerobic condition, nitrification sharply decreased, so that nitrate availability limits denitrifications.decreased, so that nitrate availability limits denitrifications.